OPTIMIZING SUSTAINABLE GEOPOLYMER PRODUCTION: INTERGRATING REACTIVE ULTRAFINE FLY ASH (RUFA) AND RECYCLED FINE AGGREGATE (RFA) - Setiawan, Preza; Wei, Ting Lin; Ummati, Alfinna Mahya; Wirawan, Nugraha Bintang (Applied Research on Civil Engineering and Environment (ARCEE), 2025)
Construction waste presents considerable risks to human health, safety, and the environment, alongside escalating expenses related to waste management and carbon emissions. Cement manufacturing provides a substantial share of carbon emissions within the construction sector. Geopolymers present a sustainable substitute for conventional cement-based concrete, capable of reducing CO2 emissions and promoting a circular economy. This study investigates the incorporation of Reactive Ultrafine Fly Ash (RUFA) and Recycled Fine Aggregates (RFA) in the production of geopolymers to create sustainable construction materials. The study investigates the physical characteristics, setting time, fluidity, compressive strength, and microstructure of RUFA geopolymers with varying quantities of RFA. The results indicate that incorporating RFA improves compressive strength, with peak results at 40% RFA content. Furthermore, RFA decreases setting time to a specific limit, beyond which additional quantities have negligible effects. Fluidity is maximized in RFA mixtures at 30%, subsequently declining. Scanning electron microscopy analysis revealed microstructural enhancements and increased density in 40% of RFA samples. Statistical analysis indicates the substantial impact of RFA content and sample age on compressive strength. This research offers significant insights into developing sustainable construction materials and underscores the necessity of carefully selecting RFA content. Future research may investigate various combinations and parameters for wider applications in sustainable construction practices.